Entrepreneurial Business: An Empirical Study of Antecedents and Consequence of Customer Satisfaction Towards Beauty Clinic - Watthanasuebsin, Taksadhon; Minakan, Nawin; Chaipoopirutana, Sirion (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study examines the factors influencing customer satisfaction at Rakta Clinic, a leading beauty clinic in Ratchaburi, Thailand, which offers a holistic range of services including injections, treatments, cosmetic surgery, and skincare. Despite the growing popularity of aesthetic services, the industry faces intense competition, rapid technological advancements, particularly in anti-aging innovations, and increasingly diverse customer expectations. While several prior studies have addressed service quality in healthcare and beauty contests, research specifically tailored to the comprehensive and multidimensional environment of aesthetic clinics remains limited. This study aims to address this gap by integrating a broad range of variables relevant that consist of nine variables: personnel support, clinic facilities, physical environment, personnel quality, technical quality, medical service quality, nursing service quality, corporate image, and customer satisfaction to beauty clinic operations, thereby offering a more contextualized understanding and contributing to improved competitiveness within the aesthetic service sector.